Using spaceborne SAR and ground-based measurements to identify spatial patterns in soil moisture and seasonal thaw timing in permafrost environments of Alaska - Baxter, W. Brad; Hoppinen, Zachary; Lasko, Kristofer; Meehan, Tate; Brodylo, David; Sullivan, Taylor D.; Barker, Amanda J.; Douglas, Thomas A. (Frontiers in Remote Sensing, 2025)
Spatiotemporal patterns in soil moisture play a critical role in the near-surface energy balance in permafrost regions, yet soil moisture detection in periglacial environments is complicated by highly heterogeneous terrain conditions. We integrate ground-based and spaceborne microwave methods to investigate patterns and controls on surface soil moisture (SSM) in boreal and arctic permafrost environments of Alaska. Soil sampling, geophysics, and probing revealed heterogeneous SSM with significant fine-scale (1 m) variability by topographic setting (p < 0.001) and pedological characteristics (p = 0.01) in arctic tundra, and by land cover type (p < 0.001) in low-relief boreal forest. SSM spatial autocorrelation was greatest below 20 m thresholds demonstrating the adequate spatial resolution for capturing natural SSM heterogeneity at these sites. SMAP L-band was tested for coarse (9 km) soil moisture detection in boreal forest but demonstrated low representativeness from limited ground-based measurements. Finer resolution (∼20 m) relative SSM derived from Sentinel-1 C-band time series in arctic tundra more closely represents the noted SSM autocorrelation length and is explored for visualizing SSM landscape variability. Satellite detection biases created by high-profile tussocks and thick organic soil horizons identified with probe-SSM reveal the need for site-specific soil information in satellite-SSM interpretations. Lastly, time-series of C-band backscatter distributions in boreal forest demonstrated potential for tracking soil thaw onset beneath residual spring snowpack. These results illustrate the complexity of SSM monitoring in periglacial environments and the potential for C-band backscatter and L-band SMAP for large-scale tracking of SSM in these environments.